“Como a raça acontece”: uma análise da incriminação por tráfico em Belo Horizonte - Daniely Roberta dos Reis Fleury (2021)
The present work is a study that articulates race relations and the Brazilian justice system in order to understand how the accused's race interferes in the incrimination process for drug trafficking in Belo Horizonte. As an empirical basis, we used quantitative data from trafficking processes closed in Belo Horizonte during the period from 2007 to 2017 and qualitative data from interviews with legal operators who worked in the capital's toxic’s court. The general objective was to investigate the operationalization of racism in the criminal justice system from three meanings: ideological, practical and structural, with a focus on trafficking processing, since this is the offense appointed as the one that targets the black population of crime-fighting policies and mobilizes a bellicose discourse capable of justifying extreme measures of control and repression. We point out that there is a set of historically constituted beliefs and values that construct blacks as “standard suspects”, racist ideologies that circulate in the field of the criminal justice system. Practices during the processing of the trafficking offense are also marked by different treatment of blacks; not only the actions of the police, but also of other actors in the judiciary (re)produce biases that contribute to the racial selectivity of the system. Furthermore, the structural dimension of racism explains how racial and socioeconomic conditions are articulated to the disadvantage of black people and also have a negative impact on the criminal justice system. The consequent effect is the continuous and mass incarceration of a racially delineated population profile. With this work, we hope to contribute to advancing the understanding of how racism is expressed in the criminal justice system, especially when it comes to the crime of drug trafficking.